EVALUATION OF POSTOPERATIVE PAIN IN PRESERVATION AND ELECTVE DISSECTION OF THE ILIOINGUINAL NERVE IN INGUINAL HERNIOPLASTY - Spasova, Zanita Jovanovska; Shapova, Biljana Todorovska; Lukovska, Elizabeta Obocki; Kikerkov, Igor; Pavlovska, Kristina; Zhogovska, Elizabeta; Slaninka Miceska, Maja (Journal of Morphological Sciences; Vol 6 No 1 (2023): JMS, 2023)
The use of mesh techniques in the treatment of inguinal hernias significantly reduce recurrences. However the incidence of  inguinodinia still present significant complication. The study was designed as a randomized, prospective, unilaterally blind clinical study. Forty male patients were included, to whom hernioplasty by Lichtenstein method with implantation of polypropylene mesh was performed. Patients were divided into 2 groups of twenty patients each. In first one the technique of the ilioinguinal preservation was used, and in the second one dissection of the ilioinguinal nerve was performed. At appropriate time points two types of scales were used to assessed the intensity of the pain: Numeric scale of pain (NSP) and Stanford pain scale (SPS).Data from 40 patients have been analyzed, of which 20 with preservation and 20 with dissection of the ilioinguinal nerve. Inguinodynia was present in two patients, one in each group, i.e. 5%, which indicates that there was no significant difference in the occurrence of inguinodynia in the group with preservation and dissection of the ilioingvinal nerve. No single direction can yet be given as to whether it is better to preserve or dissect the inguinal nerves, and there is also division over whether, if a neurectomy should be performed, it should be limited to the IIN or a triple neurectomy should be performed. Key words: inguinodinia, inguinal hernia, mesh techniques.   https://doi.org/10.55302/JMS2361024js